PKM PENINGKATAN KAPASITAS DAN KEBERDAYAAN MASYARAKAT DI DESA SUNGAI KUPAH KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Arkanudin, Arkanudin (FKIP Universitas Wisnuwardhana, 2023)
Abstract:Sungai Kupah Village is a coastal area and directly faces the South China Sea. The villagers' main source of livelihood and income is from agricultural products, especially coconut and areca nut commodities. The villagers of Sungai Kupah grow areca nut by intercropping with their coconut plantations. The coconut and areca nut crops are not yet reliable sources of livelihood. This means that it cannot be used as a support to improve community welfare. The method of implementing this PKM is carried out in three stages, namely First, conducting field orientation, Second, implementing PKM activities, Third, conducting evaluations. The results achieved in this PKM activity have provided benefits to the community, this can be seen from the response submitted by the community which is quite positive and hopes that there will be a continuation of similar activities by involving stakeholders in an integrated manner.